KidZania Surabaya Marketing Communication Strategy in Increasing the Number of Visitors - Fatma Endah Cahyaningrum; Windri Saifudin (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to determine how the marketing communication strategy used by KidZania Surabaya in increasing the number of visitors. The competitive artificial tourism industry makes companies compete to win the hearts of their consumers. This makes marketing communication strategies important to increase sales for KidZania Surabaya. This research method uses a qualitative approach, while data collection techniques are obtained through in-depth interviews, observation and documentation. The results of the study show that KidZania Surabaya has implemented various marketing communication strategies to increase the number of visitors. Some strategies used include the use of conventional and digital media as a means of promotion and publication. In addition, KidZania Surabaya also collaborates with various parties such as educational institutions and the government in the form of events that can increase public brand awareness and influence their interests and actions in buying tickets. Not only that, KidZania Surabaya also collaborates with various other companies to offer price promotions so that they can stimulate consumer purchases. The implementation of an integrated and innovative marketing communication strategy makes KidZania Surabaya able to compete with the predetermined segmentation.